Design of Heart Rate, Oxygen Saturation, and Temperature Monitoring System for Covid-19 Patient Based on Internet of Things (IoT) - Aldo Novaznursyah Costrada; Azizah Ghina Arifah; Inggi Dwi Putri; I Kadek Agus Sara Sawita; Harmadi Harmadi; Mitra Djamal (Universitas Andalas, 2022)
Instruments for measuring pulse rate, oxygen saturation, and body temperature for Covid-19 patients have been designed using the MAX30100 sensor and the Internet of Things (IoT)-based MLX90614 sensor. The MAX30100 sensor is used to measure pulse rate and oxygen saturation. A non-contact MLX90614 sensor is used to monitor body temperature, with an ultrasonic sensor used to set the maximum distance between the sensor and the object. The measurement results were transferred to the database via the ESP8266 MCU node's Wi-Fi communication line. The stored data can be accessed via a web browser. Compared to the oximeter, the MAX30100 sensor has an average error rate of 1.027% for pulse measurement and 0% for oxygen saturation. The MLX90614 sensor has a 0.42% average error rate when it was compared to the thermo-gun.Thus, the measuring device can function properly and is feasible to use. Furthermore, because there is no direct contact between the human body and the sensor, the instrument can prevent Covid-19 transmission.